QCM-D study of ß-casein on silicate-PEG surfaces - Ngadi, Norzita (Asian Network for Scientific Information, 2010)
Nonspecific protein adsorption generally occurs on any solid surfaces and usually has adverse consequences. Adsorption of proteins onto a solid surface is believed to be the initial and controlling step in biofouling. Surfaces modified with end-tethered poly(ethylene glycol) (PEG) have been shown to be protein-resistant to some degree. In this study, the adsorption of ß-casein was performed on several surfaces where PEG was tethered onto stainless steel by silicate. Protein adsorption was also performed on the bare stainless steel (SS) surface for comparison. The adsorption was conducted at 23 and 40°C and pH 7.2. In situ Quartz Crystal Microbalance/Dissipation (QCM-D) was used to determine PEG adsorption kinetics, plateau PEG chain densities, protein adsorption kinetics and plateau protein adsorbed quantities. The results showed that the presence of PEG molecules reduced the adsorption of ß-casein, more than 50% than that on the bare SS surface. Interestingly, the adsorption of ß-casein on the PEG surfaces at 40°C was much lower than that at 23°C.